Case report and literature review of a rare diagnosis of ossifying renal tumor of infancy - Flannigan, Ryan Kendrick; Heran, Manraj Kanwal Singh; Oviedo, Angelica; Wong, Nathan; Masteron, John S.T. (Canadian Urological Association Journal, 2014)
One must entertain a broad differential diagnosis for infants presenting with gross hematuria. Initial workup includes urine analysis, serum laboratory values and abdominal ultrasound. We describe an infant presenting with gross hematuria found to have a calcified renal mass upon initial ultrasound and subsequent computed tomography scan. We considered a differential diagnosis of, but not exclusive to, staghorn calculi, nephroblastoma, Wilms’ tumour, mesoblastic nephroma and ossifying renal tumour of infancy (ORTI). A nephrectomy was performed, and the pathology report identified the calcified mass as an ORTI.